Antisipasi Pencegahan Bullying Sedini Mungkin : Program Anti Bullying Terintegrasi untuk Anak Usia Dini - Ririn Ambarini; Eva Ardiana Indrariani; Ayu Dian Zahraini (Universitas Islam Nahdlatul Ulama Jepara, 2018)
AbstractThe main purpose of this service is that teachers and PAUD staff can implement and implement anti-bullying programs as prevention and also anticipation in their respective schools so that teachers and PAUD staff can assist young children to develop social skills so they can interact positively and develop any efforts which can effectively help prevent and stop the emergence of intimidation in early childhood life. Implementation of Community Service is done in the form of training activities, and field assistance which is divided into four stages in a systematic and sustainable way. The methods used in the implementation of this program include training, lectures, frequently asked questions, and discussions, teaching practices and worksheets that are the participants' outputs from this training. In implementation role playing stage, teachers who are less experienced and still new, are still asking for enlightenment and examples of solutions from senior teachers and the dedication team. The result of this community services are the satisfaction of the partner, the commitment of the teachers at PAUD to prepare the RPP about bullying, and most of them use story telling and role playing to internalize the anti bullying program.